1998
DOI: 10.1083/jcb.141.5.1181
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Mad2 to Kinetochores Depends on Microtubule Attachment, Not Tension

Abstract: A single unattached kinetochore can delay anaphase onset in mitotic tissue culture cells (Rieder, C.L., A. Schultz, R. Cole, G. Sluder. 1994. J. Cell Biol. 127:1301–1310). Kinetochores in vertebrate cells contain multiple binding sites, and tension is generated at kinetochores after attachment to the plus ends of spindle microtubules. Checkpoint component Mad2 localizes selectively to unattached kinetochores (Chen, R.-H., J.C. Waters, E.D. Salmon, and A.W. Murray. 1996. Science. 274:242–246; Li, Y., and R. Ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
477
5
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 448 publications
(526 citation statements)
references
References 36 publications
(73 reference statements)
43
477
5
1
Order By: Relevance
“…Our studies show that either Mad2⌬C or GST-Mad1F10 can overcome the checkpoint in nocodazole-treated PtK1 cells where kinetochores lack both tension as well as attached microtubules. This result indicates that BubR1 is not able to maintain the spindle checkpoint independently of Mad2 function, a conclusion supported by other studies where Mad2 function was inhibited with antibodies or deleted by genetic manipulations [Canman et al, 2000;Dobles et al, 2000;Gorbsky et al, 1998;Hoyt, 2001;Kitagawa and Rose, 1999;Li and Murray, 1991;Li and Benezra, 1996;Michel et al, 2001;Waters et al, 1998]. How the kinetochore mediates inhibition of APC/C by Cdc20 via Mad2, BubR1, or a direct effect on APC/C remains an important unresolved issue [Gillett and Sorger, 2001;Hoyt, 2001;Sudakin et al, 2001].…”
Section: Comments and Conclusionmentioning
confidence: 71%
“…Our studies show that either Mad2⌬C or GST-Mad1F10 can overcome the checkpoint in nocodazole-treated PtK1 cells where kinetochores lack both tension as well as attached microtubules. This result indicates that BubR1 is not able to maintain the spindle checkpoint independently of Mad2 function, a conclusion supported by other studies where Mad2 function was inhibited with antibodies or deleted by genetic manipulations [Canman et al, 2000;Dobles et al, 2000;Gorbsky et al, 1998;Hoyt, 2001;Kitagawa and Rose, 1999;Li and Murray, 1991;Li and Benezra, 1996;Michel et al, 2001;Waters et al, 1998]. How the kinetochore mediates inhibition of APC/C by Cdc20 via Mad2, BubR1, or a direct effect on APC/C remains an important unresolved issue [Gillett and Sorger, 2001;Hoyt, 2001;Sudakin et al, 2001].…”
Section: Comments and Conclusionmentioning
confidence: 71%
“…Spindle checkpoint proteins including Mps1p, Mad1p, Mad2p, Mad3p/BubR1p, Bub1p, and Bub3p are recruited specifically to unattached kinetochores in animal cells [reviewed in Cleveland et al, 2003], and Mad2p recruitment is independent of tension [Gillett et al, 2004;Waters et al, 1998]. However, experiments in insect spermatocytes have suggested that the lack of tension signals checkpoint activation because applying artificial tension to the kinetochore of a misaligned chromosome is able to override the checkpoint arrest in this system [Li and Nicklas, 1995].…”
Section: The Spindle Checkpoint Is Activated In Response To Unattachementioning
confidence: 99%
“…However, experiments in insect spermatocytes have suggested that the lack of tension signals checkpoint activation because applying artificial tension to the kinetochore of a misaligned chromosome is able to override the checkpoint arrest in this system [Li and Nicklas, 1995]. Although stabilization of microtubules in mammalian cells with drugs such as taxol decreases tension across sister kinetochores and activates the SAC, these treatments do not visibly alter microtubule attachment to kinetochores [Skoufias et al, 2001;Waters et al, 1998]. The SAC also appears to monitor tension across sister chromatids in budding yeast, and Ipl1p is required for this response but not for SAC activation in response to a loss of kinetochoremicrotubule attachment [Biggins and Murray, 2001].…”
Section: The Spindle Checkpoint Is Activated In Response To Unattachementioning
confidence: 99%
“…These include rod (Karess and Glover 1989; Starr et al, 1998), the MAP kinases ppERK (Shapiro et al 1998; Zecevic et al 1998) and ppMEK (Shapiro et al 1998), and an APC activator protein fizzy (called cdc20/cdh1 in other organisms; Kallio et al 1998). Likewise, the protein kinase polo (Logarinho and Sunkel 1998) and a number of components of the highly conserved spindle assembly checkpoint, including Bub1 (Taylor and McKeon 1997; Taylor et al 1998; Basu et al 1999), Bub3 (Taylor et al 1998; Basu et al 1998; Martinez-Exposito et al 1999), Mad1 (Jin et al 1998; Chen et al 1998), and Mad2 (Waters et al 1998; Chen et al 1996, Chen et al 1998), are transiently kinetochore-bound.…”
Section: Introductionmentioning
confidence: 99%